A Fused Hexacyclic Ring System: Diastereoselective Polycyclization of 2, 4‐Dienals through an Interrupted iso‐Nazarov Reaction. (24th June 2019) - Marques, Anne‐Sophie; Duhail, Thibaut; Marrot, Jérome; Chataigner, Isabelle; Coeffard, Vincent; Vincent, Guillaume; Moreau, Xavier
Abstract: We report an unprecedented domino polycyclization from readily available 2, 4‐dienals and cyclic α, β‐unsaturated imines that is initiated by an iso‐Nazarov reaction. This Brønsted acid promoted reaction enables the concomitant formation of four bonds, three cycles, and four contiguous stereogenic centers to yield elaborated structures in a single operation. A range of fused hexacyclic molecules is obtained in a highly diastereoselective manner. Abstract : Ringkampf : Eine neue, durch eine Iso‐Nazarov‐Reaktion initiierte Domino‐Polycyclisierung aus leicht erhältlichen 2, 4‐Dienalen und cyclischen α, β‐ungesättigten Iminen wird vorgestellt. Die durch eine Brønsted‐Säure vermittelte Transformation ergibt polycyclische Gerüste und ermöglicht die Bildung von drei neuen Cyclen, vier neuen Bindungen und vier zusammenhängenden Stereozentren in einem einzigen Schritt.